2020
DOI: 10.5829/ije.2020.33.05b.23
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Formability of Tailor-Welded Blanks in Incremental Forming

Abstract: Steel laser tailor-welded blanks (TWBs) are produced by end-to-end joining of base sheets using different welding methods. In this article, the formability of laser TWBs of St12 and St14 with thicknesses of 1 mm and 1.5 in single point incremental forming process were experimentally and numerically investigated. First, the forming limit wall angle was experimentally determined for each of the base sheets. Then, SPIF of TWBs samples was carried out at the thinner sheet wall angle; 67°. For numerical investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This effect is caused by the fact that the thermally affected area has a higher modulus of elasticity. A high value of the modulus of elasticity and the yield strength has opposite effects on the springback [10][11][12]. TWBs are widely used in the production of household goods, packaging, or construction.…”
Section: Introductionmentioning
confidence: 99%
“…This effect is caused by the fact that the thermally affected area has a higher modulus of elasticity. A high value of the modulus of elasticity and the yield strength has opposite effects on the springback [10][11][12]. TWBs are widely used in the production of household goods, packaging, or construction.…”
Section: Introductionmentioning
confidence: 99%
“…Experiment and FEA was carried out by Neto et al [21] using circular path and found that stress and strain FEA results are in good agreement with experimental results. Researchers used analysis software like ABAQUS [22][23], LS-DYNA [24] for predicting different output parameters efficiently. Shrivastava and Tandon [25] employed Radioss as a solver for explicit simulation and HyperView and Hypergraph for post processing.…”
Section: Introductionmentioning
confidence: 99%